Postural control in gymnasts: anisotropic fractal scaling reveals proprioceptive reintegration in vestibular perturbation - Mangalam, Madhur; Seleznov, Ivan; Kolosova, Elena; Popov, Anton; Kelty-Stephen, Damian G.; Kiyono, Ken (Frontiers in Network Physiology, 2024)
Sensory corrections in dexterous postural control might manifest in temporal correlations, specifically as fractional Brownian motions whose differences are more and less correlated with fractional Gaussian noises ($fGn$s) with progressively larger and smaller Hurst exponent $H$. Traditional empirical work examines this arrangement of lower-dimensional compression of the center of pressure (CoP) along two orthogonal axes, anteroposterior (AP) and mediolateral (ML). Eyes-open and face-forward orientations cultivate greater variability along AP than ML axes, and the orthogonal distribution of spatial variability has so far gone hand in hand with an orthogonal distribution of $H$, for example, larger in AP and lower in ML. However, perturbing the orientation of task focus might destabilize the postural synergy away from its 1D distribution and homogenize the temporal correlations across the 2D support surface, resulting in narrower angles between the directions of the largest and smallest $H$. We used oriented fractal scaling component analysis (OFSCA) to investigate whether sensory corrections in postural control might thus become suborthogonal. The OFSCA models raw 2D CoP trajectory by decomposing it in all directions along the 2D support surface and fitting the directions with the largest and smallest $H$. We studied gymnasts in eyes-open and face-forward quiet posture, and results from OFSCA confirm that such posture exhibits the classic orthogonal distribution of temporal correlations. Head-turning resulted in a simultaneous decrease in this angle $Δθ$, which promptly reversed once gymnasts reoriented their heads forward. However, when vision was absent, there was only a discernible negative trend in $Δθ$, indicating a shift in the angle's direction but not a statistically significant one. Thus, the narrowing of $Δθ$ may signify an adaptive. The swift recovery of $Δθ$ upon returning to a forward-facing posture suggests that the temporary reduction is specific to head-turning and does not impose a lasting burden on postural control. Turning the head reduced the angle between these two orientations, facilitating the release of postural degrees of freedom towards a more uniform spread of the CoP across both dimensions of the support surface. This work shows that fractality might serve as a control parameter of adaptive mechanisms of dexterous postural control.